ANALISIS PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA (PIS-PK) INDIKATOR HIPERTENSI DAN KB DI DESA COMBONGAN RT 01, RT 02 DAN RT 03 - Triani Marwati; Irnafa Ratri Aisya; Aulia Alifariani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2018)
The Healthy Indonesia Program with Family Approach (PIS-PK) integrates program implementation through the 6 main components in strengthening health systems (six building blocks), namely strengthening efforts to health services, availability of health workers, health information systems, access to essential medicines, financing and leadership or government. The purpose of this study is to increase family and member access to comprehensive (promotive-preventive, curative and rehabilitative health services) and to understand the healthy family approach program with a family approach (PIS-PK). The location of this study was in Combongan Village RT 01, RT 02 and RT 03, Bantul Regency. The population in this study were residents who lived in Combongan Village, Banguntapan District, Bantul Yogyakarta. The sample in this study was all families living in Combongan Village, Banguntapan District, Bantul, Yogyakarta. The results of this study the highest coverage value found in the indicators of families having access and using healthy latrines, which is 37%. There were 5 main problems in RT 01, RT 02, and RT 03. Hypertension and family planning were the priority problems in the area. The Healthy Indonesia Program is one of the programs from the 5th agenda of Nawa Cita, namely Improving the Quality of Indonesian Human Life. The goal of the Healthy Indonesia Program is to increase the health status and nutritional status of the community through health and community empowerment efforts supported by equitable health services and financial protection